(untitled) - Rutherfoord, Andrea J. (Upper Saddle River, New Jersey, 2001)
This provides practical applications of writing in vocational/technical fields. Presenting clear, simplified explanations of key concepts and skills in written communication, Rutherfoord's guide covers the writing process in a systems approach that integrates reading, planning, writing, and revising. This books highlights: *Fourteen technical reading passages that introduce or demonstrate each writing topic *Integration of reading, writing, spelling, word usage, and vocabulary exercises and assignments in each chapter. *Complete and independent grammar and mechanics units for flexible planning and individualized study. *Exercises and models using common technical vocabulary and concepts. *Explanations of concepts in language that is easy to understand and apply. This book is designed to help readers gain a working knowledge of all the major skills for career-related communication, including e-mail, graphics, reports, business correspondence, presentations, job interviews, and resumes.New in this edition: *Updated reading passages to reflect current communication needs and practices *Updated writing topics to reflect current trends in writing, including the use of e-mail; desktop publishing, and the Internet. *Updated chapter on report-writing (with sample reports) that introduces three common business/technical documents: the descriptive report, lab report, and proposal. *New assignments that require use of the Internet for research and communication.
Keywords: Technical writing